2020
DOI: 10.3390/su12041415
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in Extreme Precipitation and Temperature Events in the Beijing–Tianjin–Hebei Region of China over the Past Six Decades

Abstract: Extreme weather events can cause a lot of damage in highly populated regions, such as in the Beijing–Tianjin–Hebei Region (BTHR) in northern China. To understand where and how extreme precipitation and temperature events are changing within the BTHR, data for 1959–2018 from 25 mereological stations were used to detect trends in the intensity, frequency, and duration of these events. The results showed that intensity, accumulated amount, the duration of extreme precipitation events, and the annual number of day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In the south of the Yangtze River, the warm indices increase significantly, and the cold indices decrease significantly in Yunnan Province but decrease insignificantly in other regions for TX10p, which is in accordance with the existing research findings [18]. The North China Plain experiences decreasing trends for cold extremes and increasing trends of warm extremes, which is in accordance with the work of Tong et al [26], who found that both the frequency of extreme hot and cold events increases and decreases respectively in this region. Warm extremes and cold extremes show increasing and decreasing trends over northeastern China, which is consistent with the findings of Yu and Li [57].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the south of the Yangtze River, the warm indices increase significantly, and the cold indices decrease significantly in Yunnan Province but decrease insignificantly in other regions for TX10p, which is in accordance with the existing research findings [18]. The North China Plain experiences decreasing trends for cold extremes and increasing trends of warm extremes, which is in accordance with the work of Tong et al [26], who found that both the frequency of extreme hot and cold events increases and decreases respectively in this region. Warm extremes and cold extremes show increasing and decreasing trends over northeastern China, which is consistent with the findings of Yu and Li [57].…”
Section: Discussionsupporting
confidence: 91%
“…Although the variability of temperature extremes has been the focus of attention during the past several decades, most of the previous studies concerning the changing trends of the temperature extremes have ignored their spatial patterns, characteristics and spatiotemporal heterogeneity [10][11][12][13][14][15][21][22][23]52]. Moreover, existing studies mainly relied on the methods of linear trend analysis, Mann-Kendall test and Pearson correlation analysis but failed to consider the spatial and temporal effects in the methods [26,29,53,54]. In this study, we provide a comprehensive investigation of the spatiotemporal variations of the four temperature extremes by using Mann-Kendall test and a spatiotemporal model with respect to covariates from the perspectives of both humans and nature, and this approach incorporates the spatial and temporal effects of extreme indices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extreme rainfall will have a huge impact on the local ecology, industry, and social economy, which has motivated more and more studies to emphasize the importance of extreme rainfall. However, the temporal and spatial distributions of extreme weather events in different regions are quite different (Sridhar et al, 2013;Weldegerima et al, 2018), normally, with different impact ranges, frequencies, durations, and severities (Swain et al, 2019;Fagnant et al, 2020;Tong et al, 2020;Ndlovu et al, 2021). Therefore, it is of great significance to investigate the spatiotemporal variations of extreme rainfall and its potential driving factors for different regions.…”
Section: Introductionmentioning
confidence: 99%